2000
DOI: 10.1083/jcb.151.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Protein Ligands to Hur Modulate Its Interaction with Target Mrnas in Vivo

Abstract: AU-rich elements (AREs) present in the 3′ untranslated regions of many protooncogene, cytokine, and lymphokine messages target them for rapid degradation. HuR, a ubiquitously expressed member of the ELAV (embryonic lethal abnormal vision) family of RNA binding proteins, selectively binds AREs and stabilizes ARE-containing mRNAs in transiently transfected cells. Here, we identify four mammalian proteins that bind regions of HuR known to be essential for its ability to shuttle between the nucleus and the cytopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
341
1
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(360 citation statements)
references
References 91 publications
11
341
1
3
Order By: Relevance
“…Generally, the nuclear export of bulk poly(A) 1 mRNA is mediated in metazoans by the transport receptor NXF1/Tap, together with its small cofactor Nxt1/p15 (reviewed in detail in [30,[53][54][55]). However, it has also been reported that, for example, c-fos mRNA, or the message encoding interferon-a1, is translocated from the nucleus to the cytoplasm by a completely unrelated transport pathway [34,56]. This pathway is characterized by the export receptor : 70 mM) for 3 h. After 1 h, the respective cultures were activated with PMA/ ionomycin as before.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the nuclear export of bulk poly(A) 1 mRNA is mediated in metazoans by the transport receptor NXF1/Tap, together with its small cofactor Nxt1/p15 (reviewed in detail in [30,[53][54][55]). However, it has also been reported that, for example, c-fos mRNA, or the message encoding interferon-a1, is translocated from the nucleus to the cytoplasm by a completely unrelated transport pathway [34,56]. This pathway is characterized by the export receptor : 70 mM) for 3 h. After 1 h, the respective cultures were activated with PMA/ ionomycin as before.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, this interaction induces the CRM1-dependent cytoplasmic accumulation of CD83 mRNA [32]. In this respect, it is important to note that the interaction of HuR and CRM1 is indirect [34] and is, particularly in case of CD83 mRNA export, accomplished by the HuR protein ligand APRIL (ANP32B) [35]. APRIL belongs to the growing family of ANP32 proteins (ANP32a-h), a group of leucine-rich phosphoproteins that have been linked to various cellular activities such as, for example, gene expression, signaling, adhesion and apoptosis [36].…”
Section: Introductionmentioning
confidence: 99%
“…LANP proteins typically contain leucine-rich repeat motifs followed by an acidic carboxyterminal tail and are heat-stable, and are involved in a variety of biological pathways, including signaling, protein degradation, cytoskeletal dynamics, and morphogenesis, presumably based on the ability of the leucine-rich repeat (LRR) domains to serve as adapter sites for protein-protein interactions. 23,24 Previous biochemical studies suggested that human LANP (pp32/I 1 PP2A/ mapmodulin/HPPCn) has been implicated in a number of cellular processes in both nucleus and cytoplasm, including proliferation, 24 differentiation, 23 caspase-dependent and caspase-independent apoptosis, 25 suppression of transformation in vivo, 26 inhibition of protein phosphatase 2A, 27 regulation of mRNA trafficking and stability in association with HuR, 28 and inhibition of acetyltransferases as part of the INHAT complex. 29 In this report, we found that rhHPPCn may stimulate the DNA synthesis and proliferation of hepatocytes and hepatoma cell lines and activate kinase pathways including SPK, ERK1/2, and Stat3.…”
Section: Discussionmentioning
confidence: 99%
“…28 HNS is mainly responsible for nuclear/cytoplasmic shuttling upon binding adaptor proteins for nuclear export such as pp32/PHAP-I and APRIL 29,30 and with import factors transportin-1, -2 and importin a: [31][32][33] Previous Electrophoretic Mobility Shift Assay (EMSA)-based report 34 suggests that the RRM23 linker, together with the RRM3 domain, could also have an additional role in stabilizing HuR-AREs complexes. This enhancement of ARE-binding activity was greater than that observed in Surface Plasmon Resonance (SPR) experiments with HuD, a highly homolog protein to HuR, 35 where the RRM23 linker showed a negligible effect in RNA binding.…”
mentioning
confidence: 99%